Pathways from assaultive violence to post-traumatic stress, depression, and generalized anxiety symptoms through stressful life events: longitudinal mediation models. Issue 14 (3rd May 2017) - Lowe, S. R.; Joshi, S.; Galea, S.; Aiello, A. E.; Uddin, M.; Koenen, K. C.; Cerdá, M.
Abstract : Background: Assaultive violence events are associated with increased risk for adverse psychiatric outcomes, including post-traumatic stress (PTS), depression, and generalized anxiety. Prior research has indicated that economic, legal, and social stressors that could follow assaultive events may explain the increased risk for adverse psychiatric outcomes, yet longitudinal studies have not adequately examined this pathway. In the current study, we aimed to address this limitation. Methods: Participants ( N = 1360) were part of a longitudinal population-based study of adults living in Detroit. At three waves, participants indicated their exposure to assaultive violence and economic, legal, and social stressors, and completed inventories of PTS, depression, and generalized anxiety. Longitudinal mediation models were used to test the hypothesized pathway from assaultive violence to each psychiatric outcome. Results: The hypothesized models evidenced good fit with the data and, in each, the paths from Wave 1 (W1) assaultive violence to W2 stressors, and from W2 stressors to W3 symptoms were significant (range of Standardized Estimates: 0.09–0.15, all p < 0.01). Additionally, the indirect paths from W1 assaultive violence to W3 symptoms were significant (range of Standardized Estimates: 0.01–0.02, all p < 0.05). Conclusions: The findings illustrate that the economic, legal, and social stressors that could follow assaultive violence increase risk for a range of psychiatric symptoms. Although future research is needed, the results suggest that investment in interventions that prevent and mitigate assaultive violence survivors' exposure to such stressors may be an effective way to prevent mental illness in the aftermath of violent assaults.